Educational building conditions and the health of users (Construction Economics and Building, 2016)
In order to maintain a healthy learning environment, diagnosis and management of defects in the educational facility are paramount. The preliminary results of the ongoing research reported here seek to identify defects associated with educational buildings and their effects on the health of polytechnic students and staff in Nigeria. A questionnaire survey, including 34 defects based on a post-occupancy evaluation (POE) was used to establish relationships with the health of polytechnic students and staff. Two hundred (200) respondents were randomly selected based on their schools (faculty) within Lagos State Polytechnic. Descriptive and inferential statistics were used for analysis of the collected data. The results of the study indicate that defects such as plumbing and dampness problems, cobwebs and dust, are prominent in the institution. Also the relationship between building conditions (defects) and health problems was established, with the predictors of the health problems. Based on the findings, it is important for designers and managers of facilities within tertiary institutions to develop and implement design and maintenance policies targeted at minimizing the likelihood of plumbing, dampness, electrical, cobweb and dust problems in educational buildings due to the health risks induced by the defects. It is evident that effective maintenance schedules and policies should be put in place to ensure that facilities are not left to decay before replacement.